Progress Towards Implementation and Development of a New Zealand National Vertical Datum - Amos, Matthew; Featherstone, Will; Blick, G. (Springer, 2005)
New Zealand currently uses 13 disparate vertical datums, each connected to a separate tide gauge. In 1998, a new national datum, NZGD2000, was implemented based on GPS observations. This leads to a 3D geocentric datum. As further development of the spatial infrastructure in New Zealand, Land Information New Zealand approved the implementation of a new national vertical datum that is independent of local mean sea level. This new national vertical datum will be based on ellipsoidal heights, and the relationship between the separate existing vertical datums relative to the ellipsoid will be established using a high-precision regional gravimetric geoid model. Phase one of this programme is the development of a regional geoid model for New Zealand. This paper will present the current status of development of the regional geoid model. Two geoids have been computed to determine the effectiveness of a 'gravity reconstruction technique' in New Zealand. The models computed are based on a combination of the EIGEN-2 satellite-only global geopotential model,which uses CHAMP dedicated satellite gravity data,and EGM96. Residual geoid undulations were computed from 40,000 land gravity observations and satellite altimeter-derived marine gravity anomalies. GPS and first-order spirit levelling data was used in conjunction with the geoid model to estimate offsets among the 13 vertical datums.